Transfusion requirements in patients with gastrointestinal bleeding: a study in a Blood Unit at a referral hospital - A. Garrido; J. L. Márquez; F. J. Guerrero; M. A. Pizarro; E. Leo; A. Giráldez (Revista Espanola de Enfermedades Digestivas)
Objectives: 1. To study transfusion requirements in the Department of Gastroenterology of a Tertiary Referral Hospital, and their evolution over the last seven years. 2. To analyze risk factors associated with greater erythrocyte transfusion requirements. Patients and methods: erythrocyte transfusion requirements were compared for patients admitted to the Department of Gastroenterology at Hospital Virgen del Rocío, Seville, from 1999 to 2005. Clinical data of interest have been analyzed in order to determine factors associated with greater transfusion requirements. Results: 1,611 patients with a mean age of 60.45 years (59.7-61.2) were included in this study; 76.41% were males. Gastric ulcers were the cause of bleeding in 18.4% of cases (with 69% requiring transfusions); duodenal ulcers caused 22.2% of cases (with 52.9% requiring transfusions), and portal hypertension caused 33.6% of cases (with 90.2% requiring transfusions). Upper and lower gastrointestinal bleeding of unknown origin requires transfusions in 88.9 and 96.2% of cases, respectively. A multivariate logistic regression analysis showed that clinical presentations such as hematemesis (odds ratio = 3.12), hematochezia (odds ratio = 33.17), gastrointestinal hemorrhage of unknown origin (odds ratio = 6.57), and hemorrhage as a result of portal hypertension (odds ratio = 3.43) were associated with greater transfusion requirements for erythrocyte concentrates. No significant differences were observed between the percentages of patients who received transfusions from 1999 to 2005. Conclusions: 1. No differences have been observed between the percentages of patients who received transfusions over the last seven years at our Department of Gastroenterology. 2. Patients presenting with hematemesis or hematochezia, in addition to those with bleeding of unknown origin or from portal hypertension, are prone to have greater transfusion requirements.